2010
DOI: 10.1111/j.1600-6143.2009.02881.x
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Subcutaneous, Intramuscular and Inhaled Insulin Resistance Treated by Pancreas Transplantation Alone

Abstract: Diabetes mellitus with resistance to insulin administered subcutaneously or intramuscularly (DRIASM) is a rare syndrome and is usually treated with continuous intravenous insulin infusion. We present here two cases of DRIASM in 16 and 18 years female patients that were submitted to pancreas transplantation alone (PTA). Both were diagnosed with type 1 diabetes as young children and had labile glycemic control with recurrent episodes of diabetic ketoacidosis. They had prolonged periods of hospitalization and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Most likely, these factors play a role in failure of engraftment and/or requirement of a larger mass to effectively control blood glucose. Although studies support these theories, pancreas transplant does not seem to be affected by the same limiting factors and one organ is enough in fully reestablishing glucose homeostasis in diabetic patients (49,54). When islet auto-transplantation is performed in patients undergoing a pancreatectomy, the number of IEq/Kg seems to be lower when compared to allo-transplantation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most likely, these factors play a role in failure of engraftment and/or requirement of a larger mass to effectively control blood glucose. Although studies support these theories, pancreas transplant does not seem to be affected by the same limiting factors and one organ is enough in fully reestablishing glucose homeostasis in diabetic patients (49,54). When islet auto-transplantation is performed in patients undergoing a pancreatectomy, the number of IEq/Kg seems to be lower when compared to allo-transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Islet transplantation outcomes have improved over time with better success rates at one year post-transplant (3,50,51). Pancreas transplantation has been proven successful; and it is now confirmed that one pancreas is sufficient to treat diabetes regardless of insulin resistance, duration of diabetes, and other pre-existing conditions (49,54). On the contrary, most of the time, islets from at least two human pancreata are needed to reverse diabetes in a type-1 patient (6,9,50) evidencing that some major limitations to this procedure and its clinical applicability still exist.…”
Section: Introductionmentioning
confidence: 99%
“…Outra possibilidade seria o aumento da degradação da insulina no tecido subcutâneo (2) pela ação de duas principais enzimas: insulinase e proteína dissulfide isomerase (3). No entanto, sua fisiopatologia permanece desconhecida e por isso inúmeros tratamentos propostos até o momento mostram-se ineficazes (4).…”
Section: Discussionunclassified
“…IABs may result in insulin resistance and therefore cause hyperglycemia [105]. In a case study of SC insulin resistance in 7-yr old boy with type 1 DM, it did not prevent sufficient absorption of insulin from Exubera without deteriorating the patient pulmonary function [106].…”
Section: Immunogenicitymentioning
confidence: 99%